2021
DOI: 10.1136/bmjdrc-2021-002537
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes technologies for children and adolescents with type 1 diabetes are highly dependent on coverage and reimbursement: results from a worldwide survey

Abstract: IntroductionTo study healthcare professionals’ (HCP) perceptions on decision making to start insulin pumps and continuous glucose monitoring (CGM) systems in pediatric type 1 diabetes.Research design and methodsAn electronic survey supported by the International Society for Pediatric and Adolescent Diabetes (ISPAD) was disseminated through a weblink structured as follows: (1) HCP’s sociodemographic and work profile; (2) perceptions about indications and contraindications for insulin pumps and (3) for CGM syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This finding suggests that while conducting CGM training for medical staff, it may be necessary to invite relevant patients and healthcare personnel to participate in the training to increase their awareness related to CGM. 37 38 The insurance coverage of CGM-related expenses has been advocated in the literature. 13 39 For instance, the Australian government fully covers CGM-related costs for patients with DM under 21 years old and those with gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that while conducting CGM training for medical staff, it may be necessary to invite relevant patients and healthcare personnel to participate in the training to increase their awareness related to CGM. 37 38 The insurance coverage of CGM-related expenses has been advocated in the literature. 13 39 For instance, the Australian government fully covers CGM-related costs for patients with DM under 21 years old and those with gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 35 36Similar to the studies conducted in the USA, Korea and other countries, head nurses in this study agreed that the factors hindering the use and management of CGM include patients’ limited knowledge about CGM (60.2%), the high costs of CGM and inaccessibility to medical insurance (59.0%) and the non-standardised CGM management systems (44.6%). This finding suggests that while conducting CGM training for medical staff, it may be necessary to invite relevant patients and healthcare personnel to participate in the training to increase their awareness related to CGM 37 38. The insurance coverage of CGM-related expenses has been advocated in the literature 13 39.…”
Section: Discussionmentioning
confidence: 99%
“…Universal adoption of insulin delivery technologies has not occurred, with wide variation in implementation among centers, even those with similar populations 92 . A Pediatric Diabetes Consortium study of 8 US clinical centers demonstrated frequency of pump use within the first year after diagnosis ranged from 18% to 59% of participants 93 .…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…Further potential barriers to uptake of the technology voiced by those with diabetes have included concerns regarding the physical footprint and interference of the device, therapeutic effectiveness of the technology and, to a lesser extent, financial burdens this mode of insulin delivery may cause 95 . In some countries, non‐coverage, or incomplete coverage of pump therapy by the health care/insurance system likely influences the low adoption rates of this technology 15,92 …”
Section: Insulin Pumpsmentioning
confidence: 99%
“…Besides, there are studies in the literature related to the benefits and shortcomings of other systems like artificial pancreas systems [ 15 ], defined by many authors as the “holy grail” of closed-loop systems. Advances in Artificial Intelligence domain provide the basis to achieve an almost complete control on the disease, although the massive use of existing “closed” systems still depends on multiple factors surrounding patients, governments, and their environments [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%